A Qualitative Review of Literature on Peer Review of Teaching in Higher Education: An Application of the SWOT Framework. (March 2014) - Thomas, Susan; Chie, Qiu Ting; Abraham, Mathew; Jalarajan Raj, Sony; Beh, Loo-See
The issues of professional accountability, faculty member development, and enhancing higher education quality in universities are gaining importance. A strategy that could increase personal control over teaching practices in addition to improving professional development among faculty members is peer review of teaching (PRT). Five themes that are important in determining the feasibility of PRT are (a) benefits of peer review in developing faculty members, (b) barriers to peer review of teaching, (c) gaps in literature, (d) potential problems to teaching practice, and (e) opportunities. Of the 65 studies identified, 34 were selected for further analysis, and drawing on PRT and the SWOT (strength, weakness, opportunity, and threat) framework, 27 studies were selected for content mapping. Textual narrative synthesis was used to further categorize the review findings into the four quadrants of the SWOT framework. This analysis highlights a positive strategy in promoting PRT in higher education.